Croatian Civil Capacities for Peace Operations - Bosanac, Gordan (Journal of Regional Security, 2018)
This article gives an overview of the current Croatian policies as well as the legal and institutional framework related to the deployment of civilians in peace operations. It aims to explore the challenges and opportunities for further development of the existing framework to support the current political interest for civilian capacities that exists in Croatia. The article argues that most of the present state activities related to deployment of civilians in peace operations are a result of EU and NATO accession processes. It also explores the challenges in the mindset of decision and policy makers in understanding Croatia more as a security provider, rather than security receiver and questions to what extent, or how fast, the post-conflict state may be transformed into an important player in the peace building arena. The challenges are analysed through state implementation of international development cooperation as a foreign policy tool.